Bond strength of resin cement to zirconia treated in pre-sintered stage. (October 2018) - Ebeid, Kamal; Wille, Sebastian; Salah, Tarek; Wahsh, Marwa; Zohdy, Maged; Kern, Matthias
Abstract: Purpose: Aim of this study was to evaluate the tensile bond strength (TBS) between resin cement and zirconia surface treated in different sintering stages. Materials and methods: Eighty zirconia discs having final dimensions of 12 mm diameter and 3.2 mm thickness were milled then divided into three main groups according to the type of surface treatment performed (group 1: air abrasion using 50 µm Al2 O3 particles, group 2: silica coating using Rocatec soft, and group 3: a control group receiving no surface treatment). Groups 1 and 2 were divided into two subgroups each according to the stage in which the surface treatment was performed (subgroup A; surface treatment performed in the pre-sintered stage and subgroup B; surface treatment performed in the post-sintered stage). Discs were later bonded to composite core materials using resin cement then tested for TBS either being subjected to 3 days of water storage or 150 days of water storage and 37, 500 thermal cycles. Results: Long-term aging caused a significant decrease in TBS of all subgroups except the subgroup air-abraded in the post-sintered stage. After long-term aging, the group silica coated in the pre-sintered stage showed the significantly lowest TBS compared to all other groups. There was also no significant difference between the subgroups air-abraded and silica coated in the pre-sintered stage. All specimens in the control group debonded during long-term aging. Significance: Air-abrading zirconia with Al2 O3 at a reduced pressure in the pre-sintered stage may result in durable bond strength to resin cement.